Pemphigus Paraneoplastik pada Timoma : [Pemphigus Paraneoplastic in Thymoma: A Rare Case] - Herley Windo Setiawan; Daniel Maranatha (Faculty of Medicine Universitas Airlangga, 2018)
Thymomas are mediastinal primary tumour of the mediastinum and associated with a variety of autoimmune disorders often linked to T-cell mediated autoimmunity. Paraneoplastic pemphigus (PNP) is an immunologically mediated skin disease characterized by epidermal blisters that may occur in association with thymic or non thymic neoplasms. Case: 21 years old man came to the hospital with vesicles and ulcer in oral cavity and extended to whole body since 3 weeks before. Patient was diagnosed with Pemphigus vulgaris and thymomas since 2 years. Patient was hospitalized for 3 times with same cases. Patient underwent chemotherapy Carboplatin-Etoposide 6 series and Radiotherapy 25 series and no response had been documented. Patient was suggested to undergo a resection of thymoma to prevent the exacerbation of pemphigus but he refused. The medication given was only aimed for reducing the exacerbation of Pemphigus. Discussion: PNP is characterized by the production of autoantibodies against various target antigens, mainly plakin family proteins and desmogleins. PNP results from an antitumor immune response cross-reacting with the normal epithelial proteins and thereby inducing autoimmunity by molecular mimicry. PNP sera bind to homologous region within carboxyterminus of members of the plakin gene family. There are also involvement of dysregulation of T-cell development. Conclusion: Pemphigus is rarely associated with Thymomas, but the fact there is an association between Thymomas and pemphigus. According to this fact, every patients with pemphigus should be suspected with malignancies especially thymomas until it was ruled out.